Geoinformation support of geoportals of territorial communities: pre-war realities and post-war prospects - Achkasov, Anton; Popovych , Nataliia; Peresadko, Vilina; Gordeziani, Tengiz (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2024)
Problem statement. Ukraine has a wide and diverse experience in the creation of cartographic support, implementation of geoinformation systems, databases and web mapping as client-service technologies and geoportals. However, the requirements and quality criteria for local geoportals have not yet been formed, and there is no single methodology that would allow optimizing the procedure for creating geoportals at the local level and meet the competence of state managers and specialists. There is also no single unified list of mandatory cartographic works that should visualize information about the state of the country's regions. Therefore, there is a need to describe certain ready-made solutions, possible options for the structure and content of a local geoportal, advantages and disadvantages of using different software in the process of creating geoportals. High-quality geoinformation support of communities is necessary for the sustainable development of cities and communities, which is one of the Sustainable Development Goals adopted by the United Nations in 2015.The purpose of the research is to determine further prospects and directions for the development of local geoportals in Ukraine and their geoinformational and cartographic support on the basis of the analysis of regulatory documents and the experience of creating geoportals.Results. The article highlights the state, experience and prospects of implementing geoportals in Ukraine; their structure, possible functionality and cartographic content; the process of geoportal development and filling with geodata. Different software solutions for geoportal architecture based on Open Source have been compared. Using the case study of the development of a prototype of the geoportal of the Nova Vodolaha territorial community, it has been proved that with the help of open software it is possible to implement a service for interactive maps in a few steps. The advantages of the chosen architectural solution are interoperability, simplicity, visibility, the possibility of integrating data layers from national and regional sources.Practical significance. Based on the study, the following recommendations have been formulated for the development of geoportals of territorial communities: usage of open software; compliance with the principles of traditional cartography in the development of cartographic works; implementation of functions for convenient work with spatial information on the geoportal; compliance with the requirements and methodological recommendations regarding the quality, compatibility and subsequent publication of spatial data in the system of National Spatial Data Infrastructure. The proposed recommendations and architectural solutions can be applied to any local geoportal.